An Enhanced Intelligent Handheld Instrument with Visual Servo Control for 2-DOF Hand Motion Error Compensation. (16th October 2013) - Aye, Yan Naing; Zhao, Su; Ang, Wei Tech
The intelligent handheld instrument, ITrem2, enhances manual positioning accuracy by cancelling erroneous hand movements and, at the same time, provides automatic micromanipulation functions. Visual data is acquired from a high speed monovision camera attached to the optical surgical microscope and acceleration measurements are acquired from the inertial measurement unit (IMU) on board ITrem2 . Tremor estimation and canceling is implemented via Band-limited Multiple Fourier Linear Combiner (BMFLC) filter. The piezoelectric actuated micromanipulator in ITrem2 generates the 3D motion to compensate erroneous hand motion. Preliminary bench-top 2-DOF experiments have been conducted. The error motions simulated by a motion stage is reduced by 67% for multiple frequency oscillatory motions and 56.16% for pre-conditioned recorded physiological tremor.